Association between periodontitis and the prevalence and prognosis of prediabetes: a population-based study - Liao Tan; Jie Liu; Zhaoya Liu (Journal of Translational Medicine, 2023)
Abstract Background Diagnosis and intervention of prediabetes is an emerging method for preventing diabetic progression and complications. Periodontitis has been reported to strongly correlate with the dysregulation of glucose metabolism. Nonetheless, the relationship between periodontal status and the prevalence of prediabetes as well as its prognosis remains elusive. This study aimed to investigate the association of periodontitis with the prevalence of prediabetes and furtherly explore the all-cause mortality of different periodontal status among patients with prediabetes. Methods The dateset from the National Health and Nutrition Examination Survey (NHANES) was utilized for our study. Participants were divided into two groups (with or without periodontitis) and further assigned into subgroups by different grades of periodontitis to analyze the association between periodontitis and prevalence of prediabetes. Then we analyzed the association between all-cause mortality and periodontitis among patients with prediabetes. Weighted multivariate logistic/Cox regression models were adopted in our study. Results A total of 15390 participants were included and divided into a periodontitis group (n = 5033) and a nonperiodontitis group (n = 10357). The results showed that participants with periodontitis had a higher risk of prediabetes. After adjusting for covariables, more severe periodontitis was positively related to prediabetes (moderate vs. no periodontitis: OR = 1.46, 95% CI: 1.29–1.65; severe vs. no periodontitis: OR = 1.62, 95% CI 1.31–2.01). Furtherly, we explored the association between all-cause mortality and periodontal status among patients diagnosed with prediabetes (n = 4518) and found that severe (HR = 1.806, 95% CI 1.19–2.74) and moderate periodontitis (HR = 2.42, 95% CI 1.95–3.01) were associated with elevated all-cause mortality among patients with prediabetes. Conclusions In general, the results suggest that periodontitis is positively associated with the prevalence and mortality of prediabetes. These results suggest that good management of periodontal status could be a potential strategy to reduce the occurrence and development of prediabetes.